Enabling Implementation of Earned Value Management in the Spanish Construction Industry - Sutrisna, Monty; Pellicer, E.; Torres, C.; Picornell, M. (RICS 2012, 2012)
The management of construction projects in Spain has been considered traditional and therefore need to integrate more contemporary project management techniques into its practices. The Earned Value Management (EVM) can be viewed as one of the project management techniques that represents the most fundamental principles of project management. Thus, promoting EVM as a common practice in the Spanish construction industry can be regarded an important step for the construction project management practices in Spain to increase its global competitiveness. Aiming to do so, this research project has been set to study the most appropriate way to promote the use of EVM in the Spanish construction industry. Initial findings from a questionnaire survey distributed to a sample population consisting construction practitioners in Spain are presented here. The preliminary outcomes of data analysis are discussed revealing the perception and practice of project management as well as the readiness of construction firms in potentially adopting EVM as the 'new' way of working in the Spanish construction industry. Subsequently, the most effective ways for implementing EVM in Spain can be formulated and this will support further research to recommend a set of guidelines to improve project management practices in the Spanish construction industry.